Portable/Handheld NIR sebagai Teknologi Evaluasi Mutu Bahan Pertanian secara Non-Destruktif - Widyaningrum Widyaningrum; Yohanes Aris Purwanto; Slamet Widodo; Supijatno; Evi Savitri Iriani (PERTETA, 2022)
The development of NIR technology has now reached a higher level. The transition from chemical analysis which requires a lot of time and money makes NIR technology as a technology option that is efficient, fast and does not produce waste residues. Initially, the NIR was made in a benchtop type with a large size, but now it has developed into a handheld and portable NIR. This is based on the need to detect the content of agricultural materials in real-time in the field which is not possible with benchtop NIR. The use of handheld/portable NIR technology is widely applied in agriculture to measure water content, soluble solid contents, pH, mechanical properties of agricultural materials and so on. Portable/handheld NIRs have small dimensions and are light in weight so as to provide convenience in conducting direct analysis compared to using a large benchtop type NIR. However, the accuracy, measurement sensitivity, noise level, and optical reading stability are not better than benchtop NIR. So that the potential for developing portable/handheld NIRs as IoT-based sensing instruments is still open to be done.